The Differences of Students’ Ability in Writing Poetry through the Use of Constructivism Learning Method and Modeling Strategy - Efrianto Efrianto; Afnita Afnita; Ridha Hasnul Ulya (STAI Hubbulwathan Duri, 2024)
This study investigates differences in poetry writing skills between students taught using the constructivism learning method and those taught using the modeling method. The research explores the effectiveness of these methods in enhancing creativity and writing proficiency. Employing a quantitative experimental design with a 2x2 factorial framework, the study selected one class as the experimental group (constructivism method) and another as the control group (modeling method). A cluster random sampling technique was used to select 56 students from the Faculty of Language and Arts at Universitas Negeri Padang. Data were collected through performance tests, using a poetry writing assessment rubric that evaluated both physical and inner elements of poetry. Data analysis included normality and homogeneity tests and a 2-way ANOVA. The findings reveal significant differences between the two learning methods. The experimental group (constructivism) scored higher (81.57) compared to the control group (modeling), with an average of 78.14. Additionally, students with high creative thinking skills performed better (79.85) than those with lower creativity (72.57). The results confirm that the constructivism learning model is more effective in improving poetry writing skills than the modeling method. It fosters creativity and enhances students' ability to engage deeply with poetic elements. Adopting the constructivist learning approach can significantly enhance students’ poetry writing skills and creativity. Educators are encouraged to implement this method to foster greater student engagement and improved learning outcomes in creative writing.